Analysis of The Effect of Healthy and Healthy Life and Health (PHBS) Behavior of Tuberculosis Events - Purwanto, Eko (Universitas Muhammadiyah Gresik, 2020)
Tuberculosis is globally classified as a global public health Emergency. Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. East Java is ranked 2nd after West Java in TB case finding and Sidoarjo Regency is a District with the 3rd CDR achievement in East Java. The magnitude of public health problems due to Tuberculosis so that WHO provides an ultimatum with global warnings, in the Millennium Development Goals agreement aimed at freeing the world from Tuberculosis by 2050 clean and healthy life. This research was conducted with the aim of knowing how much influence the healthy home and clean and healthy living behavior on transmission and contracting TB disease. In this study using multivariate analysis by means of multiple linear regression test with a sample of 388 families where the method of sampling by means of Probability sampling is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as sample members. The method of taking with simple random sampling is a technique to get samples that are directly carried out on the sampling unit [1], analysis with the Multiple Linear Regression test by looking at the coefficient of determination (Ajusted) and the value of the beta regression (β). Tests carried out using a significant level <0.05% or 5%. The results of this study from households whose homes did not meet health requirements were found to be as much as 18.0% which in one year there were family members suffering from tuberculosis and in households that did not apply Clean and Healthy Behavior (PHBS) there were 18.8% in 1 year there are family members who suffer from tuberculosis.